Subterahertz dielectric relaxation in lead-free Ba(Zr,Ti)O3 relaxor ferroelectrics - D. Wang (Nature Portfolio, 2016)
Relaxor ferroelectrics possess potential microwave frequency applications due to characteristic dielectric relaxation properties however the underlying mechanism is debated. Here, the authors use first-principles-based molecular dynamic simulations to understand such behaviour in Ba(Zr0.5Ti0.5)O3.